ANALISIS PENGARUH LEVERAGE, AKTIVITAS DAN SIZE PERUSAHAAN TERHADAP PROFITABILITAS (STUDI KASUS PADA INDUSTRI OTOMOTIF DAN KOMPONENNYA DI BURSA EFEK INDONESIA PERIODE 2005-2011) - B11106133, Pamela Pratiwi (Jurnal Manajemen Update, 2013)
This study aimed to examine whether there is a significant effect of the Debt to Capital Assets Ratio (DCAR), Total Assets Turnover (TATO) and Size, either partially or simultaneously on Return On Total Assets (ROA). The data used in this study were obtained from Published Financial Statements of Automotive Companies Listed on the Stock Exchange in the period 2005 to 2011. The number of the study population was 13 and the number of sample companies 12 companies with the passing stage purposive sampling. The research method used is descriptive method in the form of case studies. The analysis technique used is multiple linear regression and hypothesis testing using t-statistics for testing the partial regression coefficients and F-statistics to test the effect together with the level of significance of 5%. From the results of the regression analysis can be concluded that the partial, the DCAR, TATO and Size variables have a significant effect on ROA. Simultaneously, the three independent variables, namely DCAR, TATO and Size has a significant influence on ROA. Predictive ability of these three variables on ROA companies at 50,4%, while the remaining 49,6% is influenced by other factors not included in the research model. The results of this study it is expected that the variable Debt to Capital Assets Ratio (DCAR), Total Assets Turnover (TATO) and Size can be used as a guide, either by the management company in the management of the company, as well as by investors in determining the investment strategy. Keywords : Debt to Capital Assets Ratio (DCAR), Total Assets Turnover (TATO), Size and Return On Assets (ROA)